CRIBLAGE DES POLYSACCHARIDASES CHEZ DES SOUCHES D’ACTINOMYCETES - Hanachi Hassiba; Keriem Meriem (My University, 2021)
Polysaccharides are very varied and numerous, their degradation requires a wide variety of enzymes. Bacteria, essentially actinomycetes, are capable of producing very efficient enzymatic systems acting in synergy to degrade these polysaccharides. Among these enzymes of the glycoside hydrolase type are amylases, cellulases and xylanases which were particularly studied during this work. In the context of research and screening of enzymatic activities in strains of actinomycetes, five strains were isolated from the Souk-Ahras region so their polysaccharide activity was sought. The different morphological and biochemical characters of the strains studied allowed them to be linked to actinomycetes, Gram-positive filamentous bacteria. We have used enzymatic tests by several qualitative methods based on coloring phenomena using specific reagents. Detection of enzymatic activity on solid medium reveals clear halos around the colonies. The results of this screening confirm the production of polysaccharide enzymes by the strains studied, moreover the strains S351, S331 and the strain S551 are the most active for the production of amylases, cellulases and xylanases respectively. The enzymatic activity of strains of actinomycetes on liquid medium based on specific substrates was evaluated by the Miller test. This study made it possible to select the strains S351, S331 and the strain S551 as the most producing amylases, cellulases and xylanases with activities of 21.60 IU / ml, 10.08 IU / ml and 25.11 IU / ml respectively. This study made it possible to confirm the results of the qualitative tests. ------------------------------------------------------------------------------------------ السكريات متعددة ومتنوعة للغاية ويتطلب تحللها مجموعة متنوعة من الإنزيمات. البكتيريا ، بشكل أساسي الأكتينوميست، قادرة على إنتاج أنظمة إنزيمية فعالة للغاية تعمل في تآزر لتحلل هذه السكريات. من بين هذه الإنزيمات من نوع جليكوزيد هيدرولاز الأميلازات، السليلازات والزيلانازات التي تمت دراستها بشكل خاص خلال هذا العمل. في سياق البحث وانتقاء الأنشطة الأنزيمية في الأكتينوميست، تم عزل خمس سلالات من منطقة سوق أهراس لذلك تم البحث عن نشاط عديد السكاريد. سمحت الخصائص المورفولوجية والكيميائية الحيوية المختلفة للسلالات المدروسة بربطها بالأكتينوميست البكتيريا الخيطية إيجابية الجرام. لقد استخدمنا الاختبارات الأنزيمية بعدة طرق نوعية تعتمد على ظواهر التلوين باستخدام كواشف محددة. يظهر اكتشاف النشا ط الأنزيمي على وسط صلب عن وجود هالات واضحة حول المستعمرات. تؤكد نتائج هذا الفحص إنتاج إنزيمات عديد السكاريد بواسطة السلالات المدروسة ، علاوة على أن السلالات 351 , 331 و551 هي الأكثر نشاطًا لإنتاج الأميلاز والسيليلاز والازيلاناز على التوالي. تم تقييم النشاط الأنزيمي لسلالات الأكتينوميست على وسط سائل بناءً على ركائز معينة بواسطة اختبار ميلر. مكنت هذه الدراسة من اختيار السلالات 351 , 331 و551 باعتبارها أكثر إنتاجًا للأميلاز ,السيليلاز والإزيلاناز مع أنشطة 21.60 وحدة دولية/مل , 10.08 وحدة دولية/مل و 25.11 وحدة دولية/مل على التوالي. مكنت هذه الدراسة من تأكيد نتائج الاختبارات النوعية. ----------------------------------------------------------------------------------------------------- Les polysaccharides sont très variés et nombreux, leur dégradation nécessite une grande diversité d’enzymes. Les bactéries essentiellement les actinomycètes sont capables de produire des systèmes enzymatiques très performants agissant en synergie pour dégrader ces polysaccharides. Parmi ces enzymes de type glycosides hydrolases en trouve les amylases, les cellulases et les xylanases. Dans le cadre de la recherche et le criblage des activités enzymatiques chez des souches d’actinomycètes, cinq souches ont été isolées de la région de Souk-Ahras ainsi leur activité polysaccharidiques a été recherchée. Les différents caractères morphologiques et biochimiques des souches étudiées ont permis de les rattachées aux actinomycètes bactéries filamenteuses à Gram positif. Nous avons eu recours à des tests enzymatiques par plusieurs méthodes qualitatives basées sur des phénomènes de coloration à l’aide des réactifs spécifiques. La détection de l’activité enzymatique sur milieu solide fait apparaître des halos clairs autour des colonies. Les résultats de ce criblage confirme la production des enzymes polysaccharidiques par les souches étudiées, par ailleurs les souches S351, S331 et la souche S551 sont les plus actives pour la production des amylases, les cellulases et les xylanases respectivement. L’activité enzymatique des souches d’actinomycètes sur milieu liquide à base des substrats spécifiques a été évaluée par le test de Miller. Cette étude a permis de sélectionner les souches S351, S331 et la souche S551 comme les plus productrices des amylases, les cellulases et les xylanases avec des activités de 21.60UI/ml,10.08UI/ml et 25.11UI/ml respectivement. Cette étude a permis de confirmer les résultats des tests qualitatifs.